The Impact Of Board Size On The Performance Of Shariah Compliant Companies In Malaysia - Rosnia Masruki; Mustafa Mohd Hanefah; Mohd Marzuki Ismail (Blue Eyes Intelligence Engineering & Sciences Publication, 2024)
International Journal of Recent Technology and Engineering (IJRTE) ISSN: 2277-3878, Volume-8 Issue-4, November 2019